2008
DOI: 10.1074/jbc.m805727200
|View full text |Cite
|
Sign up to set email alerts
|

The Apolar Channel in Cerebratulus lacteus Hemoglobin Is the Route for O2 Entry and Exit

Abstract: The major pathway for O 2 binding to mammalian myoglobins (Mb) and hemoglobins (Hb) involves transient upward movement of the distal histidine (His-64(E7)), allowing ligand capture in the distal pocket. The mini-globin from Cerebratulus lacteus (CerHb) appears to have an alternative pathway between the E and H helices that is made accessible by loss of the N-terminal A helix. To test this pathway, we examined the effects of changing the size of the E7 gate and closing the end of the apolar channel in CerHb by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 57 publications
2
59
0
Order By: Relevance
“…, which is close to the diffusion limit (32,38,51,61 , effectively blocking the E7 channel, and there is a roughly monotonic decrease in the rate of NO binding with increasing size of the E7 side chain for other mutants. Scott et al (17) carried out a much more extensive mutagenesis mapping study of Mb using 90 mutants at 27 different positions, and their results confirmed quantitatively the E7 gate mechanism for ligand entry into Mb, which was originally developed using just E7 mutations (60).…”
Section: E7 Gate Appears To Be the Pathway For Ligand Entry Into Hba-mentioning
confidence: 99%
See 1 more Smart Citation
“…, which is close to the diffusion limit (32,38,51,61 , effectively blocking the E7 channel, and there is a roughly monotonic decrease in the rate of NO binding with increasing size of the E7 side chain for other mutants. Scott et al (17) carried out a much more extensive mutagenesis mapping study of Mb using 90 mutants at 27 different positions, and their results confirmed quantitatively the E7 gate mechanism for ligand entry into Mb, which was originally developed using just E7 mutations (60).…”
Section: E7 Gate Appears To Be the Pathway For Ligand Entry Into Hba-mentioning
confidence: 99%
“…Kinetic Measurements of O 2 , CO, and NO Binding-Parameters for O 2 binding to the Hb E7 mutant tetramers and monomers were measured using laser flash photolysis of the stable HbCO complex in O 2 /CO mixtures to avoid prolonged exposure to oxygen and autoxidation (32). Descriptions of the 0.5-s dye laser system and sample preparations are given in supplemental Section B.…”
Section: Methodsmentioning
confidence: 99%
“…CO rebinding to the unliganded intermediates transiently formed after ligand photodissociation was followed after a 0.5-s excitation pulse from a Phase-R model 2100B dye laser, as described in previous work (35,46,47).…”
Section: Methodsmentioning
confidence: 99%
“…Alternate topological features such as interior gas tunnels in truncated hemoglobins, for example, have been shown to be mechanistically important for modulating ligand migration (18,19). However, further studies are needed to fully understand how these related protein frameworks within the globin family contribute to variations in ligand-binding properties.…”
mentioning
confidence: 99%
“…Recent structural studies conducted on noncanonical globins have greatly expanded our knowledge of how globins function (18)(19)(20)(21)(22)(23). Alternate topological features such as interior gas tunnels in truncated hemoglobins, for example, have been shown to be mechanistically important for modulating ligand migration (18,19).…”
mentioning
confidence: 99%